The psychology of early institutional economics: The instinctive approach of Thorstein Veblen's conspicuous consumer theory - Felipe Almeida (EconomiA, 2015)
Thorstein Veblen, a founder of original or old institutional economics, combined social and evolutionary thought in his institutionalist approach to dealing with psychological, social, and economic issues. The psychological content of Veblen's writings takes instinct and habits into consideration. The economic literature on the psychological content of Veblen's writings has focused on habits, despite the importance of instincts in Veblen's works. This paper attempts to discuss Veblen's notion of instincts in order to make its role clearer in his approach to conspicuous consumer decision making. It discusses the role of instincts, the instinct of workmanship, the relationship between habits and instincts, and their influence on the conspicuous consumer. Consequently, this paper contributes to a better understanding of how inner forces and socialization culminate in behavior in Veblen's conspicuous consumer approach. – – Thorstein Veblen foi um dos fundadores da Economia Institucional Original ou Velha Economia Institucional. Em seus escritos, Veblen associou as lógicas social e evolucionária em sua abordagem institucional – contemplando elementos da Psicologia, da Sociologia e da Economia. O conteúdo psicológico dos escritos de Veblen considera instintos e hábitos. A literatura econômica sobre o tema tem seu foco na análise dos hábitos, apesar da importância dos instintos na obra de Veblen. Este artigo discute a noç\~ao de instintos para Veblen em busca de esclarecer o papel dos instintos na tomada de decis\~ao do consumidor conspícuo vebleniano, o papel dos instintos, o instinto do trabalho eficiente, a relaç\~ao entre hábitos e instintos e sua influência sobre o consumidor conspícuo. Consequentemente, este texto contribui para uma melhor compreens\~ao de como impulsos internos e o processo de socializaç\~ao culminam no comportamento do consumidor conspícuo de Veblen.
Keywords: B15; B52; 330; Thorstein Veblen; Instincts; Instinct of workmanship; Institutional economics; Leisure class